Education on childrens complex care needs in general nursing curricula in Europe: An inductive content analysis. (March 2021) - Clancy, Anne; Olaso, Elena Montañana; Larkin, Philip; Brenner, Maria
Abstract: Nursing programmes must prepare children's nurses to respond effectively to the health needs of children and young people. The aim of this study was to examine general nursing curricula for child-related content. A non-experimental descriptive study design was used. Curricular plans from 18 countries where general nursing education was the only requirement to care for children with complex care needs in the community were analysed. Curricula were obtained from institutions who educated the largest number of student nurses in each country. An inductive analysis of the curricula was carried out. Almost three-quarters of the curricula (n = 13) offered one or more compulsory core modules on children. The content varied from one to sixteen ECTS credits showing a wide variation in the focus on children in these curricula. In 12 of the 18 countries most of the child-related content was in other modules. The sample curricula from five countries had no compulsory modules on children. Child-related curricular content varied considerably across countries, with little content focused on children with complex care needs. This can illustrate that nurses are not always adequately prepared to meet the needs of sick children. Highlights: Child related content in general nursing curricula varies considerably across Europe. Little content focused on children with complex care needs. There is a need to ensure that general nurses receive adequate basis training in nursing children. Unacceptable variation in number and content of modules on children in nursing curricula. Nurses' preparedness for practice to deliver care to children in the community requires further study.